Cus efflux system and resistance to nanoparticles. - Khanal, P. (The Young Researcher)
This study aimed to determine how the deletion of the cusC gene influences E. coli growth in a medium containing silver nanoparticles. Two strains of E. coli were ordered, one of which had a de- letion of the cusC gene, and were placed into four culture tubes each, which all contained nanopar- ticles. A quantitative approach and a posttest-only control group design were executed to compare the growth of the two strains by measuring the tubes’ optical densities (ODs) every hour while in school. A smooth line curve showed that the strain without the cusC gene ceased growth after some time while the parent strain continued to grow, and inferential statistics showed that a manipulated factor caused the difference in the final OD values of the strains. Thus, the deletion of the cusC gene appeared to reduce bacterial resistance when exposed to nanoparticles. This information can be used in the development of future therapeutics.